The Effect Of Attitude, Perception, Infrastructure On Dental Health Behavior In 6th Grade Of Primary School Students - Mery Novaria Pay; Novianti P Baunsele; Melkisedek O Nubatonis (Jurnal Kesehatan Gigi, 2022)
ABSTRACTBackground: Behaviourwas the result of the interaction of external factors in the form of stimuli and internal factors in the form of responses. Dental health behaviourwas very influential on attitudes, perceptions, infrastructure and behaviour. The purpose of the study: to determine the effect of attitudes, perceptions, infrastructure on the dental health behaviour of sixth grade students in Baumata Village, Taebenu District. Research method: an observational study with a cross-sectional design. The research subjects were 112 children with criteria including male and female, willing became respondents by filling out informed consent. The attitude, perception and behaviour variables were measured by a questionnaire using a Likert scale; infrastructure variables were measured using a questionnaire by filling in the yes and no options. The results: The results of the correlation analysis showed that the variables of attitude (p=0.000), perception (p=0.014) and infrastructure (p=0.022) were significantly related to behaviour. The results of multiple regression analysis showed that the infrastructure variable (p=0.212) had no significant effect on behaviour. Attitude (p=0.000) and perception (p=0.010) variables had a significant effect on behaviour. Conclusion: There was an influence of attitudes and perceptions while infrastructure has no effect on dental health behaviour in sixth grade students of SD Baumata Village, Taebenu District.